Examen Especial a las Cuentas por Cobrar de la Cooperativa de Transporte Loja período de Enero a Diciembre 2021 - Sánchez Maza, Janina Yajaira (2023)
This Curricular Integration Work called “SPECIAL EXAMINATION TO RECEIVABLE ACCOUNTS OF COOPERATIVE OF TRANSPORT LOJA FROM JANUARY TO DECEMBER 2021”, which has been developed according to Academic Regulations of the Universidad Nacional de Loja, as a requirement to obtain the degree and title of Accountant, and with the purpose of contributing to the decisions of the Cooperative of Transport Loja. With respect to develop the Special Examination in the Cooperative of Transport Loja from January to December 2021, according to the specific objectives, first of all, a visit was made to the Cooperative to gather and verify the general information and the financial activities. The risk matrix and the Internal Control questionnaire were made which allowed to evaluate and rate the risk level and the receivable accounts confidence. With the Internal Control evaluation to receivable accounts shows that the Cooperative has a 73.33% risk level and confidence, so the entity is complying with Internal Control provisions. Then, the work programs were prepared, as well as working papers such as narrative sheets, summary sheets and analytical ones, which contain and explaining the most important findings and their respective evidence. Finally, a report of Special Examination was prepared, in which it is made known the comments, conclusions and recommendations about the findings. As a result, in the Cooperative of Transport Loja does not exist a correct Internal Control System because it does not comply with the Internal Regulations; the payments of receivables accounts were not made in the due date; there is not charge any interest in case of default; the Cooperative does not send to their customers a confirmation about the receivable accounts statements; does not exist a training plan to the cash collection staff and there is not monthly report of receivable accounts. To sum up, the deficiencies found should be corrected by the manager and the cash collection staff management, implementing the recommendations plan suggested in the final report of this work, in order to achieve the goals and objectives proposed in the Cooperative of Transport Loja.